Estudio de Coherencia y Transporte Cuánticos en las Dinámicas Energéticas duranta la Captación de Energía Lumínica en Sistemas Fotosintéticos - González León, Roberto Andrés (2022)
The photosynthesis is one of the most studied biological processes through history. Its capacity to fix carbon into nutritional molecules is the base of all food chains. Its efficient exploitation of the solar energy inspires application such as solar cells, or synthesis of biologically important compounds. During the first miliseconds of the photosynthesis, sunlight is harvested and transfered to a reaction center, were it powers the conversion of carbon dioxide into carbohydrates and other fuel molecules. The understanding of the dynamics in this process is essential for the design of similar systems. In the last decades, ultrafast multidimensional electronic spectroscopy techniques have revealed the presence of quantum phenomena, such as quantum coherence and transport, during the energy transport in the photosynthesis, which are suggested to contribute to its unusually large efficiency. Although the presence of quantum phenomena in photosynthetic complexes can be probed empirically, its application is limited by the technique difficulty, highly expensive equipment, complex data analysis and its low transferability to in vivo samples. As such, in silico techniques provide a platform to study these phenomena without this experimental limitations. In this work, the study of the presence of quantum coherence and quantum transport in a protein-pigment complex is presented through fully computational methods. First, a methodology is developed and validated for the calculation of highly accurate spectroscopical parameters of the complex. From these, quantum master equations are used to obtain the dynamics of the excitation energy transport, and probe for the quantum effects and its prevalence, in order to elucidate mechanisms and factors that may extend their lifetime.